(untitled) (Universal International Scientific Journal, 2026)
This article analyzes modern approaches and methods in teaching physics. Starting from traditional lessons, various methods such as interactive, problem-based learning and laboratory experiments are considered. The specific advantages and disadvantages of each method are discussed in detail, as well as their impact on students’ deeper assimilation of knowledge. Metacognitive knowledge and strategies are also discussed, how they can be used in the educational process.